Configurações do desejo homoerótico na contística brasileira do século XX - Fernandes, Carlos Eduardo Albuquerque (2012)
From the conception of that literature express and problematize the social role, according to Antônio Cândido (2006), this research aimed at platting the trajectory of homoerotic desire in Brazilian literature of the 20th century, here taken as corpus by the genre short-story. It was chosen ten fiction narratives considering the decades of the 20th century: ―Pílades de Orestes‖ [1906], of Machado de Assis; ―História de gente alegre‖ [1910], of João do Rio; ―O Menino do Gouveia‖ [1914], of Capadócio Maluco; ―A Grande atração‖ [1936], of Raimundo Magalhães Jr.; ―Frederico Paciência‖ [1947], of Mário de Andrade; ―A moralista‖ [1957], of Diná Silveira de Queirós; ―Paixão segundo João‖ [1969], of Dalton Trevisan; ―Ruiva‖ [1978], of Júlio César Monteiro Martins; ―Terça-feira gorda‖ [1982], of Caio Fernando Abreu; ―Família‖ [1997], of Rubem Fonseca. The point of view of the research is orientated in a critic and diachronic perspective, by making to interlace discussions that circle the following themes: criticism and literary theories which lead the work in analyze, history of the homoerotism in Brazil and history of Brazilian literature, whose knowledge aids to understand the historic context of short-story publication, gay and cultural studies observing notions of homoerotic desire, relations of power and social-cultural transformations. The 20th century, according to Stuart Hall (1997), was a period of ruptures and changings in the way of individual comprehend themselves and linking themselves with each other, the categories of genre, sexuality, social stratum, modified themselves, the identities were fragmentized , the idea of love, friendship and privacy, as says Anthony Giddens (1997) were shifted. As this scenario of alterations crystallizes itself, literature, like discourse, which is a irreducible part of social life, is also metamorphosed. The characters of fiction constitute the basic element of analyze of the research, since they are the beings that experience the homoerotic desire, which suffer the social conflicts established on fiction and that permit to interpret the condition and the way of homoerotic life registered, subjectivized and problematized on and by short stories in discussion. The notion of desire with which it is worked considers the idea of Chauí (1990) and Sedgwick (1998) that understand the category as a set of emotions, expectations and wills which are besides the genital perspective and that evince the manner of homoerotic life. The research was developed to priorize the chapters of analyze of the short stories, to formulating discussions which take into account the construction of homoerotic character, the historic context of the time and the cultural transformations, concerning to homoerotism. In ending the research, they are presented the main configurations of the homoerotic desire in Brazilian context of the 20th century, having as exemplification the chosen narratives of these characters' intimacy and capacity of breaking or reinforce structure of power.